Erinnern müssen und Vergessen dürfen : der Nationalsozialismus aus der Perspektive Jugendlicher über 70 Jahre danach - Meyer, Katharina 1988- (Research, 2021)
More than 70 years after the end of National Socialism, the growing distance in time to historical events characterizes the examination of them. Changed family relationships, the farewell to eyewitnesses and current social discourses influence the perspectives of young people. This raises a multitude of questions: How are young people in Germany dealing with the topic more than seven decades after the Holocaust? What relevance does National Socialism have for you, what historical ideas do you have of the time and how do you experience dealing with it in Germany? The study investigates these questions empirically using the group discussion process and the Grounded Theory methodology, looks at continuities and breaks in the references to National Socialism and shows connections to identification with Germany